Students' Numeracy Literacy Ability through the Implementation of Problem-Based Learning and STEM Approach - Abbas, Nurhayati; Bito, Nursiya (Technium Social Sciences Journal, 2024)
This research describes the numeracy literacy abilities of students from the Mathematics Department, Faculty of Mathematics and Natural Sciences, Gorontalo State University in solving problems in the MNA and Boundary Conditions courses. The results of the research show that the numeracy skills of students from the Mathematics Department at Gorontalo State University who program the MNA and Boundary Conditions courses in solving mathematical problems are sufficient in using various kinds of numbers or symbols to solve daily life problems and analyzing information displayed in various forms such as graphs. , tables, charts, diagrams and so on. In general, the results of this analysis cannot be used by students to predict and make appropriate decisions. This is shown in the results that only 11.84% of students were able to use various kinds of numbers and symbols in the first question, 21.05% of students were able to analyze information displayed in various forms and only 9.21% had the ability to interpret all question analyzes to take the right decision